The Role of Economic Digitalization on Economic Performance in Indonesian - Arvianti, Ratna; Suliswanto, Muhammad Sri Wahyudi (Jurnal Ekonomi Kuantitatif Terapan, 2024)
Economic digitalization has an important role in improving the economic performance of a country. The purpose of this study is to analyze the effect of economic digitalization as measured by internet users, financial technology, electronic money, and electronic commerce on economic performance proxied using Gross Regional Domestic Product (GRDP) with a research focus on 34 Indonesian provinces during the 2019-2022 period. The method used in this study is a panel data regression model with secondary data sourced from BPS, OJK, and BI. So the best model is obtained, namely the Fixed Effect Model. Partially, the results showed that the internet users variable had a positive and significant effect on GRDP, financial technology had a negative and significant effect on GRDP, electronic money and electronic commerce variables had a negative and insignificant effect on GRDP. Simultaneously, the variables of internet users, financial technology, electronic money, and electronic commerce affect GRDP.